1976
DOI: 10.1002/j.1556-6978.1976.tb01725.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supervised Counseling on Dominance

Abstract: To ascertain the effects of supervised counselor experience on measures of dominance, graduate students were drawn from three departments at the University of Illinois, Urbana, and given the dominance and self-acceptance scales of the California Psychological Inventory and the California Fascism Scale. In the analysis of variance, the experimental group scored significantly higher (P<.05) on dominance than did the control group from pretest to posttest, and the correlation between dominance and self-acceptance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
1983
1983

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Additional research established that the supervisor is important in helping the trainee develop concreteness, genuineness, respect (Karr & Geist, 1977), and empathy (Wedeking & Scott, 1976). Ostrand (1976) measured students on the California Psychological Inventory and the California Fascism Scale and found that students who complete practicum have higher feelings of self-acceptance (an important counselor quality) than students who do not go through practicum.…”
Section: Maximizing Effectiveness Of the Practicum Experiencementioning
confidence: 99%
“…Additional research established that the supervisor is important in helping the trainee develop concreteness, genuineness, respect (Karr & Geist, 1977), and empathy (Wedeking & Scott, 1976). Ostrand (1976) measured students on the California Psychological Inventory and the California Fascism Scale and found that students who complete practicum have higher feelings of self-acceptance (an important counselor quality) than students who do not go through practicum.…”
Section: Maximizing Effectiveness Of the Practicum Experiencementioning
confidence: 99%